Enabling the Advanced Bioeconomy through Public Policy Supporting Biofoundries and Engineering Biology. Issue 9 (September 2019) - Kitney, Richard; Adeogun, Michael; Fujishima, Yoshiyuki; Goñi-Moreno, Ángel; Johnson, Richard; Maxon, Mary; Steedman, Scott; Ward, Sean; Winickoff, David; Philp, Jim
Abstract : The bioeconomy concept is proliferating globally. However, the enabling roles of biotechnology may be getting sidelined in the strategies of some countries. A goal for engineering biology is alignment with the engineering design cycle to enable more rapid commercialization. This paper considers several policy options to remove critical technical barriers to commercialization.